An overview on seismic analysis of masonry building aggregates - Formisano, Antonio; Ademovic, Naida (Frontiers in Built Environment, 2022)
Conservation of historical centres is a pressing need for Mediterranean countries, that are characterized by masonry aggregates representing the most typical construction type within cities. Masonry clustered buildings were usually designed without seismic design criteria. Moreover, the current seismic standard codes do not foresee a clear calculation method to predict their non-linear behaviour. For this reason, in this paper, a wide overview on the seismic response of masonry aggregates has been done considering analysis at different levels, from simplified large-scale evaluations to sophisticated non-linear analyses. In the former investigation kind, a vulnerability form appropriately conceived for clustered buildings has been applied to different historical centres with the aim to perform risk analysis considering both empirical approaches and real data deriving from occurred past earthquakes. In the second evaluation type, the macro-elements analysis method has been examined with reference to typical clustered buildings of the Italian territory. In particular, global assessments, performed using the 3Muri non-linear analysis program, have been performed with the final goal to derive fragility curves of structural units of masonry aggregates considering their plan position in the clustered building (end of row, internal, and corner).